2004
DOI: 10.1309/qd0k-9q1j-bh6b-5gqq
|View full text |Cite
|
Sign up to set email alerts
|

Human achaete-scute Homologue (hASH1) mRNA Level as a Diagnostic Marker to Distinguish Esthesioneuroblastoma From Poorly Differentiated Tumors Arising in the Sinonasal Tract

Abstract: Distinction of high-grade esthesioneuroblastomas from other poorly differentiated tumors arising in the nasal cavity is an important diagnostic challenge because it determines patient management and prognosis. The human achaete-scute homologue (hASH1) gene is critical in olfactory neuronal differentiation and is expressed in immature olfactory cells; therefore, it could have potential use as a diagnostic marker The aim of the present study was to determine the value of hASH1 messenger RNA (mRNA) levels in diff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
14
1

Year Published

2005
2005
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 18 publications
2
14
1
Order By: Relevance
“…MASH1/HASH1/ASCL1 is expressed in immature olfactory neurons and is critical for their development. Mhawech et al [8] showed for the first time distinct expression of ASH1/ASCL1 in all ENB samples compared with the ASH1/ASCL1 levels in poorly differentiated negative tumors. Mhawech et al found an inverse correlation between ENB grades and ASH1/ASCL1 messenger RNA levels and concluded that ASH1/ASCL1 could be a useful tool for distinguishing ENBs from poorly differentiated tumors of the sinonasal region.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…MASH1/HASH1/ASCL1 is expressed in immature olfactory neurons and is critical for their development. Mhawech et al [8] showed for the first time distinct expression of ASH1/ASCL1 in all ENB samples compared with the ASH1/ASCL1 levels in poorly differentiated negative tumors. Mhawech et al found an inverse correlation between ENB grades and ASH1/ASCL1 messenger RNA levels and concluded that ASH1/ASCL1 could be a useful tool for distinguishing ENBs from poorly differentiated tumors of the sinonasal region.…”
Section: Discussionmentioning
confidence: 96%
“…Neuroendocrine carcinomas are easily morphologically differentiated from neuroendocrine tumors in surgical material, although making this distinction can be difficult when using small biopsy specimens. The diagnostic usefulness of various transcription factors as markers that discriminate between neuroendocrine carcinomas and neuroendocrine tumors has been previously studied [4][5][6][7][8][9]. Achaete-scute homolog 1 (ASH1 in mammalians and hASH1 in humans) is a transcription factor belonging to the basic helix-loop-helix family.…”
Section: Discussionmentioning
confidence: 99%
“…It has also been shown that the human achaete-scute homolog-1 (hASH1) gene transcript, a transcription factor in neural development, is highly specific for neuroblastoma [23]. Others, however, contradicted this claim [24–26]. Therefore the status of hASH1 in differentiating tumors of the sinonasal region remains uncertain.…”
Section: Introductionmentioning
confidence: 99%
“…Currently, esthesioneuroblastomas are thought to arise from the olfactory neuroepithelium (41,49) . This is based on the location of these tumors and the expression of the neural developmental transcription factor ASCL1/hASH1 (50,51) , which is also expressed in some other tumors with neuroendocrine phenotype like small cell lung cancer and medullary thyroid cancer (51)(52)(53) . ASCL1 is essential for early development of neuronal progenitors in the olfactory epithelium and autonomic nervous system (12) .…”
Section: Discussionmentioning
confidence: 99%
“…ASCL1 is essential for early development of neuronal progenitors in the olfactory epithelium and autonomic nervous system (12) . A few studies have investigated hASH1 in esthesioneuroblastoma (50,51,54) . In two of these studies, hASH1 transcripts were detected in 7 and 4 esthesioneuroblastoma tumors (50,51) ; in a third study, expression was seen by immunofluorescense staining (54) .…”
Section: Discussionmentioning
confidence: 99%